Desectarianization: Looking Beyond the Sectarianization of Middle Eastern Politics - Mabon, Simon (The review of faith & international affairs, 2019)
Violent fragmentation in the Middle East has often been reduced to a consequence of "ancient hatreds" that pit Sunni against Shi'a. One of the more compelling arguments to understand the emergence of sectarian violence was proposed by Nader Hashemi and Danny Postel who suggest that the politics of the Middle East has undergone a process of sectarianization. This article builds upon the work of Hashemi and Postel to consider potential mechanisms to challenge this process of sectarianization, to work towards desectarianization. Drawing on interviews conducted across the Middle East and on a number of different disciplines, the article proposes a four-stage framework to facilitate desectarianization.